2005
DOI: 10.1016/s0002-9440(10)62362-0
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Thrombospondin-1 Overexpression Contributes to Autocrine Transforming Growth Factor-β Signaling in Cultured Scleroderma Fibroblasts

Abstract: The extracellular matrix (ECM) glycoprotein thrombospondin-1 (TSP-1) has been reported to activate the latent complex of transforming growth factor-beta (TGF-beta), the major effects of which in mesenchymal cells is stimulation of the synthesis of ECM. Previous reports suggested the involvement of an autocrine TGF-beta loop in the pathogenesis of scleroderma. In this study, we examined whether TSP-1 plays a role in maintaining the autocrine TGF-beta loop in scleroderma. TSP-1 expression was increased in sclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…Collectively, these findings suggest that cell surface molecules recruiting endogenous TGF-β to its receptors may be a promising candidate involved in the establishment of autocrine TGF-β signalling in SSc fibroblasts. Our previous reports indicated that latent TGF-β receptors, such as integrin αvβ517 and thrombospondin-118 were upregulated, and such abnormalities contribute to the establishment of autocrine TGF-β signalling in SSc fibroblasts 12 13 18. These cell surface molecules and impaired Smad7–Smurfs-mediated negative regulation of TGF-β signalling may co-ordinately contribute to the establishment of autocrine TGF-β signalling in SSc fibroblasts.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, these findings suggest that cell surface molecules recruiting endogenous TGF-β to its receptors may be a promising candidate involved in the establishment of autocrine TGF-β signalling in SSc fibroblasts. Our previous reports indicated that latent TGF-β receptors, such as integrin αvβ517 and thrombospondin-118 were upregulated, and such abnormalities contribute to the establishment of autocrine TGF-β signalling in SSc fibroblasts 12 13 18. These cell surface molecules and impaired Smad7–Smurfs-mediated negative regulation of TGF-β signalling may co-ordinately contribute to the establishment of autocrine TGF-β signalling in SSc fibroblasts.…”
Section: Discussionmentioning
confidence: 98%
“…The levels of receptors for TGF-β are elevated on SSc fibroblasts, permitting them to mount a robust response to endogenously produced TGF-β or to subthreshold levels of exogenous TGF-β in their environment (112,113). Furthermore, thrombospondin and α v β 3 integrins, both of which can mediate latent TGF-β activation, are elevated on SSc fibroblasts (114,115). Consistent with the autocrine TGF-β hypothesis, SSc fibroblasts show evidence of ligand-independent intracellular TGF-β signaling, with elevated expression and nuclear accumulation of activated SMAD3 (99,116) and its constitutive interaction with the p300/CBP coactivator (117,118).…”
Section: Figurementioning
confidence: 99%
“…To become functionally active, TGF-b needs to be activated from its latent state into a biologically active cytokine; such activation may occur through a spectrum of molecular processes, among which activation by aV-containing integrins plays the most important role, making them an ideal target for innovative antifibrotic therapies [108,109]. Thrombospondin is also an important activator of latent TGF-b [110,111], but is not required in all cases of tissue fibrosis, including in lung [112,113].…”
Section: Tgf-bmentioning
confidence: 99%